Surface skin protection of concrete with silicate-based impregnations:Influence of the substrate roughness and moisture - Rodrigues, M. P. (2014)
Silicate-based impregnations are often used to protect concrete against aggressive external actions. However, the understanding of several aspects concerning this type of impregnations is still rather Iimited, incIuding the influence of the concrete substrate on their performance. This paper presents reslllts of an experimental study about O) the efficacy of silicate-based impregnations to protect concrete elements, and (ii) the inflllence of the concrete substrate's characteristics on the performance of such superficial protection. Concrete specimens with two different water/cement ratios (0.40 and 0.70) were produced and, prior to the application of the impregnation, were prepared following different procedllres that created O) three different surface roughnesses (no surface preparation, 160 bar water jet and needle scalers) and (ii) three different moisture contents (3.0%, 4.5% and 6.0%). The performance ofunprotected and protected concrete specimens was assessed by means of the following procedures, indicated in EN 1504-2 standard: O) product penetration depth; (ii) water absorption by immersion; (iii) abrasion resistance; Ov) impact resistance; and (v) bond strength. Results obtained show that the silicate-based impregnation was effective in improving the resistance to water penetration and abrasion resistance, but did not improve the resistance to impacto The surface roughness and the moisture content at the instant of the application of the surface protection proved to influence the performance of the impregnation product, however such influence was dependent on the property at stake.